Establishing a Workload Productivity Target in an Outpatient Infusion Pharmacy (American Journal of Management, 2023)
Health-system pharmacies are under increasing pressure to maximize resources and improve efficiency, as the cost of healthcare is rising and reimbursement for medications is becoming increasingly complex. One strategy for optimizing efficiency is to utilize workforce productivity metrics to ensure the optimal staffing. While there have been many published examples of productivity-tracking models for health-system pharmacies in general, there are gaps in the literature on outpatient infusion pharmacy productivity metrics, as these pharmacies have unique workflow patterns and considerations. This paper describes some of those special considerations for infusion pharmacies and proposes a potential method for tracking workload productivity in a way that addresses those special factors. Also discussed are the limitations of this method, as well as areas for future exploration in tracking productivity in an infusion pharmacy.
Keywords: management; pharmacy; infusion; productivity; workload; metrics; staffing; efficiency